Asociatia Nationala a Fabricantilor de Produse de Uz Veterinar din Romania de la infiintare si pana in prezent - Valer Teusdea (Medicamentul Veterinar, 2022)
This PPT presentation briefly recalls the main moments in the history of the establishment, the evolution and development of the National Association of Manufacturers of Veterinary Products in Romania since its establishment in 2006 and until now.